PERANCANGAN SISTEM PENGENDALIAN KUALITAS PRODUK ASAM SULFAT (STUDI KASUS : PT. XYZ) - Juliani Sutikno (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2015)
PT. XYZ is a basic chemical manufacturing company which produces sulphuric acid. Qualitystandard are reffered to National Standard of Indonesia (SNI). PT. XYZ has certified the use of SNIstandard for sulphurid acid product quality. Quality control of product is supervised by technician fromPT. XYZ to ensure that only products that meet acceptable standard of quality which may be deliveredto customer in order to ensure customer satisfaction. PT. XYZ establish product specifications sulphuricacid in the production process with a concentration of at least 98,5%. Determination of sulphuric acidsproduct specification targets are too high from the referenced standard is loss and optimal quantity ofproduct produced. This study aims to measure the process capability and product specifications ofsulphuric acid establishes the right to increase the quantity of products. And then, Designing anappropriate system to control product quality sulphuric acid which has been determined. Determinationof the specifications made by processing the sulphuric acids inspection levels. Processing data usinganalytical tools of quality control, histogram charts, control charts, and a causal diagram. Result ofthe analysis compared to the quality control standard established by BSN through SNI 0030:2011.From the comparison of the data will be used to set quality standard appropriate levels of sulphuricacid. Quality control system design sulphuric acid starts from the selection of raw material supplier,controlling during the setting process until the sulphuric acid concentration through dilution water.